Monitoring molecular composition and digestibility of ripened bresaola through a combined foodomics approach. (January 2019) - Picone, Gianfranco; De Noni, Ivano; Ferranti, Pasquale; Nicolai, Maria Adalgisa; Alamprese, Cristina; Trimigno, Alessia; Brodkorb, Andre; Portmann, Reto; Pihlanto, Anne; El, Sedef Nehir; Capozzi, Francesco
Abstract: In this work, the effects of maturation time and simulated gastrointestinal digestion on the molecular and peptide profiles of "Bresaola Valtellina" were assessed through the foodomics approach, in this case food proteomics and peptidomics combined to other analytical and biological assays, aiming at depicting a holistic food quality. Human digestion of this Italian cured meat product was simulated using an in vitro static protocol and the degree of proteolysis and the in vitro bioactivity of the soluble free compounds in the digestates were evaluated by biochemical assays, e.g. SDS-PAGE, size exclusion HPLC, HPLC/MS, 1 H NMR, enzymatic and antioxidant activities. The obtained results demonstrated that in vitro gastrointestinal digestion contributed to a considerable release of myofibrillar proteins by the muscle tissue. Data from SDS-PAGE, peptidomic and size exclusion HPLC assays showed that the in vitro digestion largely degraded proteins of muscle tissue to peptides smaller than 250 Da. The released peptides were likely responsible for the inhibitory activity on amylolytic enzymes and for the antioxidant properties elicited by the gastric digestates of Bresaola. Overall, the results demonstrated the negligible role of ripening in making meat proteins more bioaccessible, whereas they confirmed the highly in vitro digestibility of meat proteins from Bresaola. This study represents a new approach merging proteomics and foodomics to evaluate the effect of ripening and in vitro digestion on the bioactivity and bioaccessibility of proteins and peptides of meat products. Graphical abstract: Unlabelled Image Highlights: In vitro digestion contributes to the release of meat myofibrillar proteins. Most of peptides in the intestinal digestates were smaller than 250 Da. Bioaccessibility of proteins is not quantitatively affected by ripening. Multiplatform foodomics enables assessment of Bresaola digestibility. Ripening affects antioxidant properties of digested Bresaola in gastric phase.